Handbook of Schizophrenia Spectrum Disorders, Volume III Therapeutic Approaches, Comorbidity, and Outcomes - Ritsner, Michael S.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2011)
A few disorders have some of the same symptoms as schizophrenia including schizoaffective disorders, schizophreniform disorder, schizotypal and schizoid personality disorders, delusional disorder, and autism (schizophrenia spectrum disorders). Since the 2000 there has been significant progress in our understanding of the early presentations, assessment, suspected neuropathology, and treatment of these disorders. Recent technological breakthroughs in basic sciences hold promise for advancing our understanding of the pathophysiology of schizophrenia spectrum disorders. This collective monograph reviwers recent researches regarding the origins, onset, course, and outcome of schizophrenia spectrum disorders. In particular, this book will be illustrate new developments in terms of conceptual models, and research methodology, genetics and genomics, brain imaging and neurochemical studies, neurophysiology and information processing in schizophrenia spectrum disorders patients. Also will be highlighted new developments in our understanding of the childhood psychosis, prodromal and first-episode states, in treatment and rehabilitation. Thus, the purpose of this book is to provide up-to-date overview of the rapid advances made in the clinical and basic science studies supporting our understanding of the relationship between cerebral processes and clinical, cognitive and other presentations of the schizophrenia spectrum disorders. In addition, this book aims to monitor important research developments, which may be relevant to treatment, and rehabilitation of patients.
Keywords: Medicine; Neurosciences; Neurology; Neurobiology; Psychology, clinical; Biomedicine; Neurosciences; Neurobiology; Neurology; Neuropsychology